Архітектурно-археологічні дослідження Десятинної церкви 2009 р. - Івакін, Г.Ю.; Іоаннісян, О.М.; Йолшин, Д.Д.; Лукомський, Ю.В. (Археологічні дослідження в Україні, 2010)
Architectural and archaeological research at Desyatynna Church in Kyiv was ongoing. Cleaning and recording of remains of the monument were made in the apse part, in the area of original kernel, north-western corner, and in front of the western façade. The data obtained testifies the continuity in the construction process at various areas of the temple. New fragments of mosaics, fresco painting, and stone carving have been discovered.